2010
DOI: 10.1186/1750-1326-5-46
|View full text |Cite
|
Sign up to set email alerts
|

Insulin deficiency exacerbates cerebral amyloidosis and behavioral deficits in an Alzheimer transgenic mouse model

Abstract: BackgroundAlthough increasing evidence has indicated that brain insulin dysfunction is a risk factor for Alzheimer disease (AD), the underlying mechanisms by which insulin deficiency may impact the development of AD are still obscure. Using a streptozotocin (STZ)-induced insulin deficient diabetic AD transgenic mouse model, we evaluated the effect of insulin deficiency on AD-like behavior and neuropathology.ResultsOur data showed that administration of STZ increased the level of blood glucose and reduced the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 78 publications
7
98
0
2
Order By: Relevance
“…Intrahippocampal insulin injection in normal rats significantly improves spatial memory ability [51]. In addition, nasal insulin in a diabetic mouse model had no effect on serum glucose levels, but improved diabetic related decline in cognitive function and changes in brain morphology and molecular pathology [52]. Long-term high fructose diets induce peripheral and central IR in rats, whereas glycine improves IR and cognitive impairment induced by fructose diets [53].…”
Section: Insulin Can Improve Cognitive Dysfunction Caused By Insulinmentioning
confidence: 99%
“…Intrahippocampal insulin injection in normal rats significantly improves spatial memory ability [51]. In addition, nasal insulin in a diabetic mouse model had no effect on serum glucose levels, but improved diabetic related decline in cognitive function and changes in brain morphology and molecular pathology [52]. Long-term high fructose diets induce peripheral and central IR in rats, whereas glycine improves IR and cognitive impairment induced by fructose diets [53].…”
Section: Insulin Can Improve Cognitive Dysfunction Caused By Insulinmentioning
confidence: 99%
“…After induced onset diabetes by administration of streptozotocin (STZ), pR5 Tg mice expressing P301L mutant Tau showed hyperphosphorylation of Tau protein in the brain (36). Also, APP/PS1 double Tg mice displayed increased severity in AD pathology involving Aβ generation, neuritic plaque formation and spatial memory deficits (37,38). These reports have suggested that experimental diabetes could exacerbate the pathology of AD in various animal models.…”
Section: Discussionmentioning
confidence: 94%
“…26,27 This is thought to be achieved by drainage of cerebral A␤ through the extracellular space via a perivascular route. 26,28 The factors influencing the clearance of A␤ are not known, although evidence suggests that it may involve various A␤ receptor transport across the blood-brain barrier, enzymes such as insulindegrading enzymes 29 and various peptides, 30 microglia, and astrocytes 31 There is some evidence to suggest that cerebrovascular disease itself may affect the elimination of A␤ protein because of loss of pulsations in thrombosed or arteriosclerotic arteries required for drainage. 32 …”
Section: Global Neocortical Pib Retention (Excluding Infarct Region)mentioning
confidence: 99%
“…More recent studies do suggest an exacerbation of A␤ amyloidogenesis and astrocytic activation in acute ischemic diabetic mice, and that this amplification colocalized with autophagosomes. 29,34 Similarly, in a middle cerebral artery occlusion model with rats fed a high-fat diet for 2 months and streptozotocin-induced type 2 diabetes showed exacerbated cognitive impairment and additively higher A␤ burden compared to control ischemic rats. 35 Furthermore, insulin-degrading enzymes soluble fraction taken from human postmortem brain tissue using a monoclonal antibody was shown to remove Ͼ85% of the A␤ degrading activity.…”
Section: Effect Of Diabetes On Pib Retentionmentioning
confidence: 99%